Gaseous Ozone Treatment Augments Chondrogenic and Osteogenic Differentiation but Impairs Adipogenic Differentiation in Human Dental Pulp Stem Cells In Vitro - Lavanya Pasalkar; Mahesh Chavan; Avinash Kharat; Avinash Sanap; Supriya Kheur; Bhonde Ramesh (Wolters Kluwer Medknow Publications, 2022)
Introduction: Stem cells have gotten a lot of attention because of their unique ability to differentiate and regenerate. Stem cells perform an important function in tissue regeneration and repair. Human dental pulp stem cells (hDPSCs) are a popular source of stem cells for accelerating wound healing. Over the last few decades, the use of ozone (O3) has progressed in medical specialties all over the world, resulting in significant clinical successes in the treatment of bone, vascular, and immunological ailments, as well as pain management. However, in the domain of tissue regeneration and differentiation, the effect of ozone on stem cells has received little attention. This is the first study to show that ozone therapy has an effect on hDPSCs. Materials and Methods: hDPSCs were isolated and grown in vitro from healthy extracted teeth. The culture media were allowed to absorb gaseous ozone. The ozone treatment was administered at concentrations of 0, 5, 10, 15, 20, 25, and 30 μg/mL, with a control concentration of 0 μg/mL. Proliferation was measured using the MTT reagent after 48 hours. The effect of ozone on the differentiation of DPSCs into osteoblasts, chondroblasts, and adipocytes was studied using the optimal ozone concentration. Results: One-way Analysis of variance (ANOVA) comparison between different concentrations of ozone showed statistically significant result (F = 23.895; P < 0.001). Maximum metabolic activity was observed with 10 μg/mL ozone. The proliferation increased up to 15 μg/mL; with further increase in O3 concentration, there was a marked reduction in proliferation. With 10 μg/mL, post-ozone treatment marked increase in osteogenic and chondrogenic. Chondrogenic differentiation was found to be statistically significant (P < 0.001) whereas marked decrease was seen with adipogenic differentiation. Conclusion: About 10 μg/mL ozonization slightly increased the proliferation in hDPSCs and distinctly increased the differentiation potential in chondrogenic and osteogenic lineages. But decreased adipogenic differentiation. With these findings, future studies will help to explain how ozonization affects hDPSCs to enhance their potency for clinical applications.